Stevens Johnson Syndrome: Past, Present, and Future Directions Gynecologic Manifestations and Management in SJS/TEN - DenAdel, Michelle A.; Hendrickson, Sarah E.; Fuchs, Esther (Frontiers in Medicine, 2022)
Stevens Johnson Syndrome (SJS) and Toxic Epidermal Necrolysis (TEN) are severe mucocutaneous hypersensitivity disorders characterized by sudden onset epidermal necrosis. Acute manifestations of SJS/TEN often include vulvovaginal erosions, ulcerations, vaginal discharge, bleeding, vaginal pain, dysuria, and urinary retention. If not treated, this can lead to complications such as vulvovaginal adhesions, vaginal stenosis or dryness, pain, dyspareunia, bleeding, and adenosis. Even with adequate treatment, there are lasting impacts including difficulty with vaginal exams and psychological distress. Early recognition and treatment of vulvovaginal involvement are crucial to preventing severe sequelae. Despite the potentially devastating consequences of genitourinary involvement of SJS/TEN, involvement of the mucocutaneous surfaces of the vulva and vagina is inconsistently documented, and protocols for treatment and follow-up are not well-established. The treatment of vulvovaginal involvement relies largely on expert opinion, and there is little data on the efficacy of suggested management. The goal of this review was to identify whether establishing a clinical pathway increased treatment of vulvovaginal SJS/TEN and to optimize our standardized protocol to prevent genitourinary sequelae. Methods We conducted a retrospective chart review of female patients with SJS/TEN at Harborview Medical Center, University of Washington from 2008 to 2021. Demographic and clinical data including gynecologic consultation, exam findings, treatment regimens, and outpatient follow-up were collected from the electronic medical record. We compared data before and after implementation of a clinical care pathway in 2017. Results We reviewed a total of 88 charts of women with possible SJS/TEN between 2008 and 2021. Of these 88 charts, 77 were found to have clear biopsy proven diagnosis of SJS/TEN. A total of 42 patients were found to have vulvovaginal involvement (55%) and gynecology was consulted in 43% of cases. 50% of patients (n = 21) with vulvovaginal involvement were recommended treatment with vaginal dilators and steroid ointment and 34% of patients with genital involvement received no treatment. Between 2008 and May of 2017 (pre-protocol), we found 55 patients with SJS/TEN. 55% of patients (n = 29) had vulvovaginal involvement (n = 26 vulvar, n = 21 vaginal). Gynecology was only consulted in 26% (n = 14) of patients. Of the 21 females with vaginal involvement, only 38% (n = 8) had dilators/vaginal molds with steroid ointment recommended. Of the 26 females with vulvar involvement, 31% (n = 8) had no vulvar treatment recommendations with the remaining 69% having some documentation that ranged from gauze placement only (19%) to topical lidocaine, barrier cream, antibiotic or antifungal cream/ ointment, lubricant, or topical steroid ointment (50%). Menstrual suppression was recommended in 38% (n = 9) of menstruating females. An antifungal medication was only prescribed in 4% of patients. Following implementation of the clinical pathway for the treatment of SJS/TEN in 2017, 22 females with SJS/TEN were identified. 72% (n = 16) had documented vulvovaginal involvement (n = 16 vulvar, n = 9 vaginal). Gynecology consultations took place in 86% (n = 19) of patients. We identified several improvements after implementation of the protocol. Gynecology consults overall increased from 26% pre-, to 86% post-protocol. For patients with vulvovaginal involvement, consultations were completed in 93% compared to 50% prior to protocol. Of note, the finding of vulvovaginal lesions increased from 53 to 72%. Dilator use with topical steroid ointment was consistently recommended, as was antifungal use and menstrual suppression. Conclusion Having a protocol in place for treatment of female patients with SJS/TEN increased the consistency of Gynecologic consultation and the documentation and treatment of vulvovaginal SJS/TEN. We identified the need to improve clinical follow-up after discharge from the hospital, which could be arranged as multidisciplinary visits and would be a good option to assess long-term outcomes (pain, sexual activity, etc.). With regards to future directions, we are in the process of assessing long-term data on quality of life and sexual functioning. The impact of treatment in the acute setting on the development of chronic sequelae needs to be established, as does the management of long-term sequelae like vaginal dryness, pain, dyspareunia. The role of local estrogen and vaginal laser still needs to be explored. Pelvic floor physical therapy might play a significant role in rehabilitation and has yet to be studied.